Additive Manufacturing Interventions during the COVID-19 Pandemic: South Africa - Thywill Cephas Dzogbewu; Sampson Afrifa Jnr; Nathaniel Amoah; Samuel Koranteng Fianko; Deon de Beer (Applied Sciences, 2021)
Additive manufacturing (AM), also known as 3D printing, is considered a renaissance of the manufacturing industry. Its unique capability of manufacturing 3D objects with intricate geometrical configurations has been used to produce hospital equipment and personal protective equipment (PPE) in an attempt to curb the spread of the COVID-19 pandemic in South Africa. The technology has been used by different research units to produce ventilators, respirator face masks, oscillating respiratory devices, oxygen connectors, oxygen splitters, non-invasive ventilation helmets, reusable clinician PPE, visor frames for face shields, etc. Despite the efforts of the AM community in South Africa, COVID-19 infections have continued to increase in the country. It came to light that technological interventions (including AM) alone cannot prevent the spread of the virus without the corresponding adaptive behavioural changes, such as adhering to COVID-19 prevention protocols (washing of hands, social distancing, etc.). It could be postulated that the spread of COVID-19 can only be prevented by inter-marrying the technological interventions (AM) with adaptive behavioural changes.